The Julian chapter [compact disc, unabridged] : a wonder story - Palacio, R. J. (Brilliance Audio, 2014)
From the very first day Auggie and Julian met, it was clear they were never going to be friends, with Julian treating Auggie like he had the plague. Over one million people have read Wonder and have fallen in love with Auggie Pullman, an ordinary boy with an extraordinary face. Now readers will have a chance to hear from the book's most controversial character: Julian.